Development of elliptic functions according to Ramanujan - Venkatachaliengar, K.; Cooper, Shaun (Singapore ; Hackensack, NJ : World Scientific, 2012)
This unique book provides an innovative and efficient approach to elliptic functions, based on the ideas of the great Indian mathematician Srinivasa Ramanujan. The original 1988 monograph of K Venkatachaliengar has been completely revised. Many details, omitted from the original version, have been included, and the book has been made comprehensive by notes at the end of each chapter. The book is for graduate students and researchers in Number Theory and Classical Analysis, as well for scholars and aficionados of Ramanujan's work. It can be read by anyone with some undergraduate knowledge of re.
The basic identity -- The differential equations of P, Q and R -- The Jordan-Kronecker function -- The Weierstrassian invariants -- The Weierstrassian invariants, II -- Development of elliptic functions -- The modular function [Lambda].
Originally published as a Technical Report 2 by Madurai Kamaraj University in February, 1988.
Includes bibliographical references and index.
Added to collection customer.56279.3
Keywords: Ramanujan Aiyangar, Srinivasa, -- 1887-1920.; Ramanujan Aiyangar, Srinivasa, -- 1887-1920; Elliptic functions; Fonctions elliptiques; MATHEMATICS -- Complex Analysis; Elliptic functions